Perlindungan Hukum Bagi Pekerja Terkait Penahanan Ijazah oleh Perusahaan dalam Hubungan Industrial - Rachman, Moch. Nur; Simangunsong, Frans (Media Hukum Indonesia (MHI), 2026)
This  study  aims  to  analyze  the  form  of  legal  protection  for  workers  concerning  the  practice  of  diploma  retention  by  companies  within  industrial  relations.  Diploma  retention  has  increasingly  appeared  in  recruitment  processes  and  employment  relations,  despite  the  absence  of  explicit  legal  grounds  in  Indonesian  labor  regulations.  This  practice  potentially  violates  workers’  fundamental  rights,  disrupts  psychological  well-being,  restricts  labor  mobility,  and  weakens  workers’  bargaining  positions  in  industrial  relations.  Using  a  normative  juridical  research  method,  this  study  examines  the  relevant  provisions  of  Labor  Law,  implementing  regulations,  principles  of  worker  protection,  and  industrial  relations  theories  to  assess  the  legality  and  implications  of  diploma  retention.  The  findings  indicate  that  the  retention  of  workers’  diplomas  by  companies  contradicts  the  principles  of  freedom  to  work,  non-discrimination,  and  the  protection  of  personal  documents.  Legal  protection  for  workers  can  be  pursued  through  administrative,  civil,  and  criminal  mechanisms,  as  well  as  dispute  resolution  procedures  under  Law  Number  2  of  2004  on  Industrial  Relations  Dispute  Settlement.  This  study  concludes  that  diploma  retention  not  only  causes  material  and  immaterial  losses  to  workers  but  also  negatively  impacts  the  harmony  of  industrial  relations.  Therefore,  consistent  law  enforcement  and  clearer  regulations  are  necessary  to  prevent  diploma  retention  practices  and  ensure  the  protection  of  workers’  rights.This  study  aims  to  analyze  the  form  of  legal  protection  for  workers  concerning  the  practice  of  diploma  retention  by  companies  within  industrial  relations.  Diploma  retention  has  increasingly  appeared  in  recruitment  processes  and  employment  relations,  despite  the  absence  of  explicit  legal  grounds  in  Indonesian  labor  regulations.  This  practice  potentially  violates  workers’  fundamental  rights,  disrupts  psychological  well-being,  restricts  labor  mobility,  and  weakens  workers’  bargaining  positions  in  industrial  relations.  Using  a  normative  juridical  research  method,  this  study  examines  the  relevant  provisions  of  Labor  Law,  implementing  regulations,  principles  of  worker  protection,  and  industrial  relations  theories  to  assess  the  legality  and  implications  of  diploma  retention.  The  findings  indicate  that  the  retention  of  workers’  diplomas  by  companies  contradicts  the  principles  of  freedom  to  work,  non-discrimination,  and  the  protection  of  personal  documents.  Legal  protection  for  workers  can  be  pursued  through  administrative,  civil,  and  criminal  mechanisms,  as  well  as  dispute  resolution  procedures  under  Law  Number  2  of  2004  on  Industrial  Relations  Dispute  Settlement.  This  study  concludes  that  diploma  retention  not  only  causes  material  and  immaterial  losses  to  workers  but  also  negatively  impacts  the  harmony  of  industrial  relations.  Therefore,  consistent  law  enforcement  and  clearer  regulations  are  necessary  to  prevent  diploma  retention  practices  and  ensure  the  protection  of  workers’  rights